Sna3 is an Rsp5 Adaptor Protein that Relies on Ubiquitination for its MVB Sorting - Macdonald, Chris (2012)
The process in which ubiquitin (Ub) conjugation is required for trafficking of integral membrane proteins into multivesicular bodies (MVBs) and eventual degradation in the lumen of lysosomes/vacuoles is well-defined. However, Ub-independent pathways into MVBs are less understood. To better understand this process, we have further characterized the membrane protein Sna3, the prototypical Ub-independent cargo protein sorted through the MVB pathway in yeast. We show that Sna3 trafficking to the vacuole is critically dependent on Rsp5 ligase activity and ubiquitination. We find Sna3 undergoes Ub-dependent MVB sorting either by becoming ubiquitinated itself or associating with other ubiquitinated membrane protein substrates. In addition, our functional studies support a role for Sna3 as an adaptor protein that recruits Rsp5 to cargo such as the methionine transporter Mup1, resulting in efficient Mup1 delivery to the vacuole.